KONSELING INDIVIDU DENGAN PENDEKATAN HUMANISTIK UNTUK MENANGANI KECEMASAN BELAJAR SISWA MADRASAH TSANAWIYAH AL - MANSYURIYAH (MTS) - Siti kamilatusholihah; Nur Azmi Wiantina; Pebrisa Amrina (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study aims to determine the condition of students’ learning anxiety of individual counseling with a humanistic approach, and the supporting and inhibiting factors in its implementation at MTS Al-Mansyuriyah. This research employed a qualitative method with a descriptive approach and a case study model. The research subject was a ninth-grade student who experienced learning anxiety. Data collection techniques were carried out through observations, interviews, and documentation using source and technique triangulation to ensure data validity. The results showed that the student experienced learning anxiety characterized by fear, nervousness, low self-confidence, difficulty concentrating, and low participation in learning activities. The implementation of individual counseling with a humanistic approach was conducted through four counseling sessions emphasizing empathy, unconditional positive regard, and a warm relationship between counselor and student. After participating in the counseling process, the student showed positive changes, including reduced anxiety, increased self-confidence, more active participation in learning, and better ability to control anxious feelings. Supporting factors in the counseling implementation included a good relationship between the counselor and the student as well as support from the school, while the inhibiting factor was the limited implementation of counseling guidance programs at school. Therefore, individual counseling with a humanistic approach was proven effective in helping overcome students’ learning anxiety at MTS Al-Mansyuriyah.